Human Response to Longitudinal Perturbations of Standing Passengers on Public Transport During Regular Operation - Krašna, Simon; Keller, Arne; Linder, Astrid; Silvano, Ary P.; Xu, Jia-Cheng; Thomson, Robert; Klug, Corina (Frontiers in Bioengineering and Biotechnology, 2021)
This study investigates the response of standing passengers in public transport that experience balance perturbations during non-collision incidents. The objective of the study was to analyze the effects of the perturbation characteristics on initial passenger responses and their ability to maintain balance. Sled tests were conducted on healthy volunteers of age 33.8±9.2 years (13 males, 11 females) standing on a moving platform facilitating measurements of initial muscle activity and stepping response of the volunteers. The volunteers were exposed to five different perturbation profiles representing typical braking and accelerating maneuvers of a public transport bus, in forward and backward directions. The sequence of muscle activations in lower extremity muscles was consistent for the pulses applied. For the three acceleration pulses combining two magnitudes for acceleration (1.5 & 3.0 m/s2) and jerk (5.6 & 11.3 m/s3), the shortest muscle onset and stepping times to recover balance were observed with the high jerk value, while the profile with the high acceleration magnitude and longer duration induced more recovery steps and a higher rate of safety harness deployment. A tendency for shorter response time was observed for the female volunteers. For the two braking pulses (1.0 & 2.5 m/s2), only the low magnitude pulse allowed balance recovery without compensatory stepping. The results obtained provide a reference data set for human body modelling, development of virtual test protocols, and operational limits for improving the safety of public transportation vehicles and users.